2014
DOI: 10.1371/journal.pone.0112970
|View full text |Cite
|
Sign up to set email alerts
|

Community Based Case-Control Study of Rotavirus Gastroenteritis among Young Children during 2008-2010 Reveals Vast Genetic Diversity and Increased Prevalence of G9 Strains in Kolkata

Abstract: BackgroundGroup A Rotaviruses are a major etiologic agent of gastroenteritis in infants and young children (<5 years) worldwide. Although rotavirus vaccines have been successfully administered in many countries, in India the introduction of rotavirus vaccine in national immunization program was approved in 2014. Since high disease burden and large number of genetic variants have been reported from low income countries including India, monitoring of rotavirus was initiated prior to implementation of the vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
4
12
0
Order By: Relevance
“…Antunes et al (24) investigated rotavirus genotypes in an unvaccinated population in northern Portugal in 2007, and they reported the most common genotype was G2P [4] with a rate of 68.6% and it was followed by G9P [8] with a rate of 14%. In South Korea, India, Japan, and Indonesia, the most common genotype was G1P [8]; it was followed by the G4P [6] genotype in South Korea, by G9P [8], G2P [4], and G9P [4], respectively, in India, by G3P [8] and G9P [8] in Japan, and by G1P [6] and G2P [4] genotypes in Indonesia (25)(26)(27)(28). The most common genotype in Brazil was reported to be G2P [4], and it was followed by the G1P [8] genotype (28).…”
Section: Discussionmentioning
confidence: 98%
“…Antunes et al (24) investigated rotavirus genotypes in an unvaccinated population in northern Portugal in 2007, and they reported the most common genotype was G2P [4] with a rate of 68.6% and it was followed by G9P [8] with a rate of 14%. In South Korea, India, Japan, and Indonesia, the most common genotype was G1P [8]; it was followed by the G4P [6] genotype in South Korea, by G9P [8], G2P [4], and G9P [4], respectively, in India, by G3P [8] and G9P [8] in Japan, and by G1P [6] and G2P [4] genotypes in Indonesia (25)(26)(27)(28). The most common genotype in Brazil was reported to be G2P [4], and it was followed by the G1P [8] genotype (28).…”
Section: Discussionmentioning
confidence: 98%
“…The other common genotypes isolated in Europe were: G4P(8), G2P(4), G9P (8), and G3P(8) [4][5][11][12]. In addition, Mullick et al [13] reported the most common genotypes as G1P(8), G9P(8), G2P(4) and G9P(4) in India, while Numazaki et al [14] identified G1P(8), G3P (8) and G9P(8) as the most frequent in Japan. In Republic of Korea, the most common genotypes were G1P(8), G2P(4) and G9P (8) in the study published by Kim et al [1], while Boula et al [15] reported G9P(8), G1P(8) and G3P(6) genotypes in Cameroon.…”
Section: Discussionmentioning
confidence: 99%
“…When the molecular study of Rotavirus begun from 2003 in Nepal by Uchida et al, in that first study G9 was not found, in subsequent studies by Sherchand et al and Ansari et al there were G9 genotypes occurrence comprising 2–6% [19, 20, 28]. Alike kind of increase in G9 has also been observed in neighboring country India, from 2 to 10% in 2003–2007 to around 40% in 2013 [35]. The increment of G9 can be because of the escape recognition by immune system of Nepalese children where G 12 was predominant in previous years.…”
Section: Discussionmentioning
confidence: 99%